Psychological Stress among Higher Secondary School Students during Covid Era in relation to Gender, Caste, and Locality - Venkateswar Meher; Laxmi Meher (International Journal of Theory and Application in Elementary and Secondary School Education, 2021)
In the present research, we have taken an attempt to study stress levels among higher secondary school students during the COVID-19 period. This research aimed at studying the psychological stress level among higher secondary students during the COVID pandemic and the variations in the psychological stress among students in terms of gender, caste, locality. It also investigated the effect of gender, caste and locality, and their interaction on the stress of higher secondary school students. The descriptive survey method was used in this study. Approximately 151 students as samples were taken for the study. The sample was delimited to higher secondary students Bargarh and Sambalpur districts of Odisha. A standardized stress scale was used to collect data. The data were collected through online mode using google form as the study was conducted in the COVID era. The obtained data were analyzed through descriptive and inferential statistical tests like percentages, t-test, and ANOVA. The findings of the study revealed that 68% of students experienced moderate levels of stress, 17% of students experienced high levels of stress, and 15% of students experienced a low level of stress. The results of the t-test indicated no significant variations in the psychological stress of secondary school students with reference to their gender, caste, and locality. The results of ANOVA revealed no significant interaction influence among gender, caste, and locality on the psychological stress of higher secondary school students. As the study was conducted in the COVID era, and demographic variables like gender, caste, and streams of education were taken altogether, so this represents the novelty of the work.